High-dimensional phenotyping of the peripheral immune response in community-acquired pneumonia - Reijnders, Tom D. Y.; Schuurman, Alex R.; Verhoeff, Jan; van den Braber, Marlous; Douma, Renée A.; Faber, Daniël R.; Paul, Alberta G. A.; Wiersinga, W. Joost; Saris, Anno; Garcia Vallejo, Juan J.; van der Poll, Tom (Frontiers in Immunology, 2023)
Background: Community-acquired pneumonia (CAP) represents a major health burden worldwide. Dysregulation of the immune response plays an important role in adverse outcomes in patients with CAP.We analyzed peripheral blood mononuclear cells by 36-color spectral flow cytometry in adult patients hospitalized for CAP (n=40), matched control subjects (n=31), and patients hospitalized for .We identified 86 immune cell metaclusters, 19 of which (22.1%) were differentially abundant in patients with CAP versus matched controls. The most notable differences involved classical monocyte metaclusters, which were more abundant in CAP and displayed phenotypic alterations reminiscent of immunosuppression, increased susceptibility apoptosis, and enhanced expression of chemokine receptors. Expression profiles on classical monocytes, driven by CCR7 and CXCR5, divided patients with CAP into two clusters with a distinct inflammatory response and disease course. The peripheral immune response in patients with CAP was highly similar to that in patients with COVID-19, but increased CCR7 expression on classical monocytes was only present in CAP.CAP is associated with profound cellular changes in blood that mainly relate to classical monocytes and largely overlap with the immune response detected in COVID-19.Community-acquired pneumonia (CAP) is a common cause of hospitalization, morbidity, and mortality. While we know that a dysregulated immune response drives the clinical manifestations of CAP, detailed knowledge on this immune response at single-cell resolution in humans is limited. This is the first study to comprehensively phenotype circulating blood leukocytes in a population of mild to moderately ill patients with CAP at hospital admission using highdimensional flow cytometry. We find an expansion of several types of classical monocytes, cellular changes previously linked to immune suppression, novel associations with chemokine receptors such as CCR7 and CXCR5, and a high degree of overlap with the immune response in patients with COVID-19. In patients with CAP at hospital admission, our results strongly suggest a role for classical monocytes, immune suppression, and chemokine receptors in disease pathophysiology. Future studies should investigate the mechanistic and potentially therapeutic implications of these findings.